Effects of alcohol-related problems on the costs of frequent emergency department use: an economic analysis of a case–control study in Spain - Oliveras, Clara; Bruguera, Pol; Cordero-Torres, Imanol; Millán-Hernández, Andrea; Pons-Cabrera, Maria Teresa; Guzmán Cortez, Pablo Rodrigo; Gómez-Ramiro, Marta; Vázquez, Mireia; Borràs, Roger; Asenjo-Romero, Maria; Vieta, Eduard; Gual, Antoni; et al. (Frontiers in Public Health, 2024)
Introduction: Alcohol-related problems increase the probability of frequent Emergency Department (ED) use. Here, we compared the direct healthcare costs of a single visit between frequent and non-frequent ED users and characterized the role of alcohol-related problems in healthcare costs generated by ED use. Methods: The study relied on secondary analyses of economic data from a 1:1 matched case-control study that had the primary aim of outlining the clinical characteristics of hospital ED frequent users in a Mediterranean European environment with a public, universal, tax-financed health system. Participants were ages 18 to 65 years and attended the ED of a high-complexity Spanish hospital (cases ≥5 times, controls <5) from December 2018 to November 2019. Each case was matched to one control with the same age, gender, and date of attendance to the ED. Clinical data and direct healthcare costs for a single ED visit were obtained by retrospective review of the first electronic medical register. Costs and length of stay were compared between cases and controls using paired-samples t-tests, and ED users with and without alcohol-related problems were compared using bivariate (independent-samples t-tests, one-way analysis of variance, Chi square tests, and multiple linear regression) and multivariate analyses (multiple linear regression models with backward stepwise selection algorithm, dependent variable: total mean direct costs). Results: Among 609 case-control pairs (total n=1218), mean total healthcare direct costs per ED visit were 22.2% higher among frequent compared with non-frequent users [mean difference, 44.44 euros (95% confidence interval 13.4–75.5); t(608) = 2.811, p=0.005]. Multiple linear regression identified length of stay, triage level, ambulance arrival, and the specialty discharging the patient as associated with total healthcare costs for frequent users. In bivariate analyses, a history of alcohol-related problems was associated with 32.5% higher mean total healthcare costs among frequent users [mean difference, 72.61 euros (95% confidence interval 25.24–119.97); t(320.016) = 3.015, p=0.003)]. Conclusions: The findings confirm the high cost of frequent ED use among people with alcohol-related problems, indicating that costs could be reduced through implementation of intervention protocols.